1987
DOI: 10.3354/meps039285
|View full text |Cite
|
Sign up to set email alerts
|

Importance of algal turf, grazers, and spatial variability in the recruitment of a subtidal colonial invertebrate

Abstract: ABSTRACT. Factors affecting the recruitment of a colonial ascidian, Pseudodistoma novaezelandiae (Brewin), were investigated in a rocky subtidal habitat at Leigh, New Zealand. The presence of coralline algal turf enhanced recruitment both in natural conditions, when standardized against adult abundance, and also in an experiment in which algal turf was removed. Removal of the large gastropod Cookia sulcata (Gmelin) and the echinoid Evechinus chloroticus (Val.) had no effect on recruitment.Recruits were aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The adults have a shell size of 3-6 mm when they are 1 year old, and they are often covered by an encrusting red algae (Calvo et al 1998;Milazzo et al 2014). The number of recruits was standardised against the surface and adult abundance because of the low dispersal ability of the crawling larvae, and also because the greater the number of adults the greater can be the number of recruits (Stocker & Bergquist 1987).…”
Section: Methodologiesmentioning
confidence: 99%
“…The adults have a shell size of 3-6 mm when they are 1 year old, and they are often covered by an encrusting red algae (Calvo et al 1998;Milazzo et al 2014). The number of recruits was standardised against the surface and adult abundance because of the low dispersal ability of the crawling larvae, and also because the greater the number of adults the greater can be the number of recruits (Stocker & Bergquist 1987).…”
Section: Methodologiesmentioning
confidence: 99%
“…Acceptable levels of precision will be specific to the question being asked. Many authors (Standen and Latter 1977;McElhone 1978;Downing 1979;Gilyarov et al 1979;Jones and Francis 1982;Way and Wissing 1982;Drake 1983;Downing and Cyr 1985;Morin 1985Morin , 1987Pont 1986;Downing et al 1987;France 1987;Stocker and Bergquist 1987;Vezina 1988;Pace et al 1991) have demonstrated that the sampling variance for sets of replicate samples of benthos, phytoplankton, and zooplankton from streams, lakes, and marine environments varies consistently as s 2 = *•*>;…”
Section: Estimates Of the Abundance Of Larval And Ju-mentioning
confidence: 99%
“…Departures from m = s2 are most acute when large numbers of organisms per sample are encoun tered in samples. Intersample s2 therefore suggests that aquatic popula- Stocker and Bergquist (1987);16, Downing et al (1987);17, 20, Frontier (1972); 21, Jones Downing and Rath (1988); 24, Downing and Anderson (1985); 25, France (1988). Table 9.2.…”
Section: Normative Data On Biological Heterogeneitymentioning
confidence: 98%